Constant Slip Rate on the Doruneh Strike‐Slip Fault, Iran, Averaged Over Late Pleistocene, Holocene, and Decadal Timescales. Issue 6 (8th June 2021) - Mousavi, Zahra; Fattahi, Morteza; Khatib, Mohammad; Talebian, Morteza; Pathier, Erwan; Walpersdorf, Andrea; Sloan, R. Alastair; Thomas, Alexander L.; Rhodes, Ed; Clive, Fynn; Dodds, Nicholas; Walker, Richard T.
Abstract: Varying estimates of both present‐day strain accumulation and long‐term slip rate on the Doruneh left‐lateral strike‐slip fault, NE Iran, have led to suggestions that it exhibits large along‐strike and/or temporal changes in activity. In this study, we make and compare estimates of slip rate measured using both geodesy and geomorphology, and spanning time periods ranging from decadal to 100 ka. To image the present‐day accumulation of strain, we process 7 years (2003–2010) of data from six ENVISAT tracks covering the fault, with interferograms produced for 400‐km‐long strips of data to image the long‐wavelength signals associated with interseismic strain accumulation across the locked fault. Our analysis shows that less than 4 mm/yr—and likely only 1–3 mm/yr—of slip accumulates across the fault. Using high‐resolution optical satellite imagery, we make reconstructions of displacement across six alluvial fans whose surfaces cross the fault, in four separate river catchments. We determine the ages of these fans using infra‐red‐stimulated luminescence dating combined with U‐series dating of pedogenic carbonates. The six fans vary in age from ∼10– to 100 kyr, and a regression line fitted to four of these yields a slip rate of 2.5 ± 0.3 mm/yr. We conclude that within the uncertainty of our measurements, the slip rate has remained constant over the last ∼100 ka and is representative of the strain accumulation at the present‐day. The slip rate that we measure is consistent with the E‐W left‐lateral Doruneh fault accommodating N‐S right‐lateral faulting by "bookshelf" faulting, with clockwise rotation about a vertical axis. Key Points: We compare present‐day strain accumulation and late Quaternary slip on the Doruneh fault, Iran We conclude that the fault has slipped at a constant rate of 2.5 ± 0.3 mm/yr throughout the last ∼100 ka